Porous hexagonal cobalt oxyhydroxide sheets with attached nickel hydroxide nanoparticles as electrode materials for electrochemical supercapacitors. Issue 20 (6th March 2015) - Wu, Mao-Sung; Tsai, Chun-Yi; Lai, Yu-Sheng
<x xml:space="preserve">Abstract</x> Ultra small Ni(OH)2 nanoparticles are directly grown on the porous conductive CoOOH sheet using cathodic electrophoresis as the high-performance electrode materials for supercapacitor application.